The modulated emission of the ultraluminous X-ray source in NGC 3379 - Fabbiano, G; Kim, D; Fragos, T; Kalogera, V; King, A; Angelini, L; Davies, R; Gallagher, J; Pellegrini, S; Trinchieri, G; Zepf, SE; Zezas, A (Institute of Physics Publishing, 2006)
We report recent Chandra observations of the ULX in the elliptical galaxy NGC 3379 that clearly detect two flux variability cycles. Comparing these data with the Chandra observation of ∼5 years ago, we measure a flux modulation with a period of ∼12.6 hr. Moreover, we find that the emission undergoes a correlated spectral modulation, becoming softer at low flux. We argue that our results establish this source as a ULX binary in NGC 3379. Given the old stellar population of this galaxy, the ULX is likely to be a soft transient; however, historical X-ray sampling suggests that the current "on" phase has lasted ∼10yr. We discuss our results in terms of ADC and wind-feedback models. If the flux modulation is orbital, we can constrain the donor mass and orbital period at the onset of mass transfer within 1.15-1.4 Ṁ and 12.5-17 hr, respectively. The duration of the mass transfer phase so far is probably ∼ 1 Gyr, and the binary has been a soft X-ray transient throughout this time. These constraints are insensitive to the mass of the accretor. © 2006. The American Astronomical Society. All rights reserved.